2020
DOI: 10.3390/cancers12020482
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in the Treatment of BRAF-Mutant Melanoma

Abstract: Melanoma is the most lethal form of skin cancer. Melanoma is usually curable with surgery if detected early, however, treatment options for patients with metastatic melanoma are limited and the five-year survival rate for metastatic melanoma had been 15–20% before the advent of immunotherapy. Treatment with immune checkpoint inhibitors has increased long-term survival outcomes in patients with advanced melanoma to as high as 50% although individual response can vary greatly. A mutation within the MAPK pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 188 publications
(173 reference statements)
1
106
0
Order By: Relevance
“…BRAF inhibitors have been shown to rapidly suppress melanoma growth and control the malignancy in a large proportion of patients [11,52,53]. Although BRAF inhibitors can induce good responses in many patients with BRAF-mutant melanoma, in some cases, a reduction in effectiveness can be observed after 7-8 months of therapy [32,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BRAF inhibitors have been shown to rapidly suppress melanoma growth and control the malignancy in a large proportion of patients [11,52,53]. Although BRAF inhibitors can induce good responses in many patients with BRAF-mutant melanoma, in some cases, a reduction in effectiveness can be observed after 7-8 months of therapy [32,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Although BRAF inhibitors can induce good responses in many patients with BRAF-mutant melanoma, in some cases, a reduction in effectiveness can be observed after 7-8 months of therapy [32,54,55]. Several mechanisms account for the reduction in tumour response to BRAF inhibitor therapy [52,53]. These include both primary (intrinsic) and secondary (acquired) mechanisms: primary applies to patients who do not respond to BRAF inhibitor therapy from the outset (approximately 15% of patients) [52]; whereas secondary mechanisms involve individuals who initially responded to BRAF inhibitor therapy, but subsequently relapsed [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanoma is the most common malignant skin tumor with a high mortality rate. Drugs targeting BRAF mutations such as vemurafenib, dabrafenib and PD-1 monoclonal antibodies, including pembrolizumab and nivolumab have greatly improved the prognosis of melanoma [ 71 , 72 ]. Gallardo treated melanoma cells with IVM and found that it could effectively inhibit melanoma activity [ 73 ].…”
Section: The Role Of Ivm In Different Cancersmentioning
confidence: 99%